Awareness and attitude toward household poisons among medical and nonmedical students: A comparative study - D Priyanka; Gurudatta S Pawar; Jayashree G Pawar; Ashutosh Baliram Potdar (Indian Journal of Health Sciences and Biomedical Research KLEU, 2018)
INTRODUCTION: There are innumerable things we use in our household on day-to-day basis. Many things that we use at home from cleaning products to cosmetics are toxic when we are not careful about them. OBJECTIVES: The study is carried out to assess and to compare the awareness and attitude of medical and nonmedical students toward household poisons and to bring awareness among the students and general public about household poisons. MATERIALS AND METHODS: A questionnaire containing 40 questions were given to the study category of students (300 students, 150 medical and 150 nonmedical), tabulated, and analyzed using SPSS 17. RESULTS: Eighty-five percent medical students and 34.7% nonmedical students are aware of the hazards caused by household poisons. Even though an awareness should be created to bring about further change in their attitude toward household poisons especially among the nonmedical students. CONCLUSION: In the present study, 84% medical students and 83% nonmedical students said that awareness about household poisons should be added in the academic curriculum. This will provide a pathway for health education to broaden a change of attitude toward household poisons.